An Estimation of the Cost of Providing Books for further Reading in Libraries of Distance Education - V. K. J. Jeevan; Kamna Trivedi (Journal of Information and Knowledge, 2022)
The Self Learning Materials (SLMs) of distance education attempt to provide learners with a learning environment containing textbooks and lecture notes. Apart from this, counselling sessions, media enabled solutions such as audio/ video channels and teleconferencing sessions are provided to learners. A small library of essential books for further reading mentioned in the SLMs are also maintained at the study centres to offer library facilities comparable to campusbased education. An accurate and efficient cost estimation and optimisation methodology is very important in library development as it would assist the management to estimate the costs involved. Cost analysis is perhaps not given the required consideration by libraries largely due to the fact that they are state-funded, and difficulties attached to assess the use made out of money spent. This study has been carried out to find out the optimum cost of supply of books prescribed for further reading in the SLMs of Master of Library and Information Science (MLIS) programme of the national Open University, IGNOU to the libraries of its Regional Centres and of its Study Centres hosting the programme.